Density, structure and spatial distribution of Brazilnut trees (Bertholletia excelsa H. & B.) on two plateaus of moist evergreen forest in the northern Brazilian Amazon - Salomão, Rafael de Paiva (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2009)
The Brazilnut tree (Bertholletia excelsa H. & B. - Lecythidaceae) is native to the Amazon River basin where it is found in non-flooding, upland forests. The nut is the best known non-timber forest product from the Amazon and has been firmly established in overseas trade for over a century as the only seed in international commerce that is collected solely from primary tropical forest. This study evaluates Brazilnut tree abundance, spatial distribution, diameter, height, and age in dense tropical rain forests on two plateaus in northern Brazilian Amazonia. The study sites, termed the Almeidas and Aviso plateaus, include forested areas of 763 and 1,365 ha, respectively, where forest inventories were made including all Brazilnut trees with dbh ≥ 10 cm. The two areas had 1,140 and seven Brazilnut trees, respectively, yielding densities of 1.5 trees/ha and 0.005 trees/ha. Percentages of young trees (dbh ≤ 60 cm) on the two plateaus were inversely related to Brazilnut tree abundense, that is 1.21% (19 trees) in higher density (Almeidas) and 71.4% (five trees) in the lower (Aviso), suggesting a recent colonization in Aviso plateau. The largest number of trees (64.1% of total) occurred within 90-160 cm of dbh, and 78 trees were recorded between 200-300 cm (6.8% in total). Today, it is rare to find Brazilnut trees with diameters up to 300 cm; the nine individuals recorded above this limit on the Almeidas plateau probably have several hundred years. The abundance of Brazilnut in Almeidas and Aviso plateaus is an intriguing question and difficult to unravel. There is the possibility to consider the anthropic origin of the Brazilnut trees in Almeidas plateau, which could be confirmed by further studies.